Waterfront redevelopment in Malaysian cities - Ismail, Sumarni; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah (AENSI Publications, 2015)
During the last three decades, the waterfront areas of many 'post-industrial' cities in North America, Britain, Europe and Australasia have undergone a remarkable transformation. Emerging from industrial degradation and from burial under transportation infrastructure, inner-urban harbours and riverfronts have been reborn as showpiece cultural and leisure precincts. The waterfront redevelopment had gone hand in hand with a broader renaissance of inner cities after decades of suburban dispersion. After decades of decline, cities are rebounding, and one key to bringing urban areas back to life is revitalizing commercial districts. Successful revitalization approaches need to capitalize on the opportunities presented in inner-city neighbourhoods while addressing long-standing obstacles to their rebirth.